2005
DOI: 10.1007/s11262-004-4587-8
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Mutations in the Genome of Echovirus 6During Establishment of a Chronic Infection in Precursors of Glial Cells

Abstract: Although Enteroviruses are mainly described as responsible for acute diseases, their role in severe chronic pathology has been also established. Echovirus 6-like sequences have been detected by PCR analysis in central nervous system specimens from patients presenting with Amyotrophic Lateral Sclerosis. These findings suggested a persistent infection with viruses that underwent, genetic changes precluding viral particle release. To support this hypothesis, we developed a model system of Echovirus 6 chronic infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…A broad range of cytolytic viruses, including enteroviruses, establish persistent types of infections both in vivo and in vitro (4,5,8,15,28,33). In most cases, this is induced by selection of virus mutants that are less cytopathic (2,20,53). Other mechanisms comprise coevolution of both cells and viruses (1,6,50).…”
Section: Discussionmentioning
confidence: 99%
“…A broad range of cytolytic viruses, including enteroviruses, establish persistent types of infections both in vivo and in vitro (4,5,8,15,28,33). In most cases, this is induced by selection of virus mutants that are less cytopathic (2,20,53). Other mechanisms comprise coevolution of both cells and viruses (1,6,50).…”
Section: Discussionmentioning
confidence: 99%
“…A murine model revealed that sequences within the 5′-UTR SL II of CVB3 are determinants of cardiovirulence and contribute to CVB3-induced heart disease ( Dunn et al, 2000 , 2003 ). Furthermore, Beaulieux et al (2005) developed a model system of echovirus 6 chronic infection and revealed two mutations in the 5′-UTR 6 months after the start of the infection: a single mutation at nt 30 in the cloverleaf and a mutation at 108 nts upstream of domain II of IRES. It is thought that these 5′-UTR mutations may help establish a persistent disease state, although the exact mechanism needs to be elucidated.…”
Section: ′- and 3′-viral Utr Rnas Influence The Course Of Infectionmentioning
confidence: 99%
“…Our results regarding the prolonged detection of enteroviral RNA in CNS of experimentally infected mice are in agreement with those of Feuer et al [5] who demonstrated that CV-B3 can persist in the CNS of infected BALB/c newborn mice up to 90 days p.i., despite the lack of infectious virus. As far as the issue of a persistent infection with echovirus, a model of E-6 chronic infection in precursors of glial cells has been described [21]. However, to the best of our knowledge, a persistent infection of CNS with E-9 has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%